Barrow holographic dark energy with Granda–Oliveros cutoff (2022)
A study on the effects of implementing the Granda-Oliveros infrared cutoff in the recently introduced Barrow Holographic Dark Energy model is presented, and its cosmological evolution is investigated. We find how the deformation parameter, Δ, affects the values of H(z), and find that from this model it is possible to obtain an accelerated expansion regime of the universe at late times. We also obtain that increasing Δ causes the EoS parameter to transition from quintessence to phantom. In addition, we show that the model can be used to describe the know eras of dominance. Finally, after studying the stability of the proposed model, a fit of the corresponding parameters is preformed, utilizing the measurements of the expansion rate of the universe, H(z). The best fit of the parameters is found to be (α,β,Δ)=(1.00+0.02−0.02,0.69+0.03−0.02,0.000+0.004−0.000) at 1σ C.L, for which the Bekenstein-Hawking relation is favored.